Seven Year Old Male with Tricuspid Endocarditis - Omar Damji; Russ A. Lam; Mark Bromley; Melanie Willimann (CINQUILL Medical Publishers Inc., 2021)
Pediatric endocarditis, a rare entity in developed countries, remains a challenging diagnosis to make in children. We present an uncommon etiology of shortness of breath on exertion (SOBOE) in a 7-year-old male presenting with two weeks of nocturnal fever, malaise and fatigue following a viral prodrome. Point of care ultrasound (POCUS) led to suspicion for a ventricular septal defect (VSD) with tricuspid valve (TV) endocarditis, which was ultimately confirmed by formal echocardiography. This ultrasound diagnosis allowed emergency clinicians to order blood cultures under the suspicion of endocarditis as well as expedited antibiotic treatment.